Plasma fatty acids and risk of colon and rectal cancers in the Singapore Chinese Health Study. Issue 1 (December 2017) - Butler, Lesley; Yuan, Jian-Min; Huang, Joyce Yongxu; Su, Jin; Wang, Renwei; Koh, Woon-Puay; Ong, Choon-Nam
Abstract Fatty acid composition in plasma captures both dietary intake and endogenous synthesis. Prospective analyses of plasma fatty acid composition are needed to establish the role of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) on risk of developing colorectal cancer. To evaluate associations between plasma fatty acid composition and colon or rectal cancer risk separately, a nested case-control study of 350 colorectal (211 colon and 139 rectal) cancer cases and an equal number of individually matched control subjects was conducted within the Singapore Chinese Health Study, a cohort of 63, 257 men and women recruited between 1993 and 1998. Fatty acids in pre-diagnostic plasma were quantified using gas chromatography–tandem mass spectrometry. Conditional odds ratios (ORs) and 95% confidence intervals (CIs) comparing highest to lowest quartiles are presented. For colon cancer, inverse associations were reported with higher essential PUFAs, α-linolenic acid (OR = 0.41; 95% CI: 0.23, 0.73;P trend  = 0.005) and linoleic acid (OR = 0.43; 95% CI: 0.23, 0.82;P trend  = 0.008). Higher desaturase activity in the n-6 PUFA synthesis pathway estimated by the arachidonic:linoleic acid ratio was associated with increased colon cancer risk (OR = 3.53; 95% CI: 1.82, 6.85;P trend  = 0.006), whereas higher desaturase activity in the MUFA synthesis pathway estimated by the oleic:stearic acid ratio was associated with decreased colon cancer risk (OR = 0.42; 95% CI: 0.19, 0.92;P trend  = 0.024). There was no significant association between the essential fatty acids or the desaturase indices and rectal cancer risk. Endogenous synthesis of arachidonic and oleic acids has an impact on colon cancer development. Colorectal cancer: Dietary fat intake shapes colon cancer risk Higher consumption of "good fats, " or their natural creation by the body, may help protect people from colon cancer. Jian-Min Yuan from the University of Pittsburgh, USA, and colleagues used samples from the Singapore Chinese Health Study to examine fatty acids contained in blood plasma from 350 people who later developed colorectal cancer and an equal number of matched control individuals. They found that higher blood levels—which reflect dietary intake—of the essential polyunsaturated fatty acids linolenic acid and α-linolenic acid were associated with a lower risk of colon cancer. So was oleic acid, a monounsaturated fat created by the body, whereas conversion of linolenic acid to another fatty acid called arachidonic acid boosted colon cancer risk. No effect was seen on rectal cancer risk. Diets rich in linolenic acid may help prevent colon cancer.